2021
DOI: 10.1021/acs.jpcc.1c05005
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Charge Transfer in Two-Dimensional Hybrid Lead Halide Perovskites

Abstract: 2D hybrid perovskites consisting of layers of lead halide octahedra separated by long organic linker cations have great potential for functional material design toward tailored optical and electronic properties. Here, we report the first direct observation of light-induced charge transfer (CT) in a series of novel 2D perovskites incorporating conjugated linkers based on the carbazole molecule. Dedicated electron paramagnetic resonance experiments and supporting quantum-chemical calculations reveal that exciton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Although it has been shown that simple aliphatic or aromatic ammonium cations (e.g., BA or PEA) can be applied toward the stabilization of the cesium lead(II) iodide black phase through dimension engineering, the insertion of more complex organic ammonium cations, potentially bestowing additional optical properties [34][35][36] and charge carrier dynamics to the hybrid, [37][38][39][40][41][42] has not been applied for the same purpose. In addition, approaches to increase the phase purity of quasi-2D hybrid perovskite films have been poorly investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been shown that simple aliphatic or aromatic ammonium cations (e.g., BA or PEA) can be applied toward the stabilization of the cesium lead(II) iodide black phase through dimension engineering, the insertion of more complex organic ammonium cations, potentially bestowing additional optical properties [34][35][36] and charge carrier dynamics to the hybrid, [37][38][39][40][41][42] has not been applied for the same purpose. In addition, approaches to increase the phase purity of quasi-2D hybrid perovskite films have been poorly investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…Goovaerts’s group observed an inorganic-to-organic hole transfer in the 2D HPs constructed by a carbazole-contained spacer molecule due to a type-II band alignment between the HP skeleton and the spacer layer . Dou’s group experimentally demonstrated the modular design of the organic energetics in n = 1 2D HPs .…”
Section: Excited-state Dynamics By Various Local Statesmentioning
confidence: 99%
“…117,118 Goovaerts's group observed an inorganic-to-organic hole transfer in the 2D HPs constructed by a carbazole-contained spacer molecule due to a type-II band alignment between the HP skeleton and the spacer layer. 119 Dou's group experimentally demonstrated the modular design of the organic energetics in n = 1 2D HPs. 115 Bithiophene unit (2T), 4Tm, 4TCNm, and BTm were utilized, and the corresponding intralayer energy landscapes are shown in Figure 8a−d.…”
Section: Singlet Level Alignmentmentioning
confidence: 99%
“…This work broadened the material system of the organic spin transport layer. Although the hybrid organic‐inorganic perovskites contain halogen and heavy elements, which have a particular impact on their spin transport performance, HOIPs still have potential applications drawn upon their excellent conductivity, [57] flexibility, and adjustable photoelectric performance [58] . Besides, there are also reports of high‐performance pure organic perovskites [59] recently.…”
Section: Organic Spin Transport Materialsmentioning
confidence: 99%